(untitled) (Bangladesh Journal of Medical Science, 2012)
Mediastinal cavernous lymphangioma is a benign rare lesion originating from lymphatic system. It is usually asymptomatic. We have presented a 2 year old male child with fever for seven days. Opacity was found in chest X-ray in the upper part of right hemithorax, merged with the mediastinum.CT scan of chest was performed, which revealed a large, lobulated, smoothly marginated non-enhancing, low density, mediastinal mass, involving right half, extending from root of neck. Finally, pathological examination of the surgical sample indicated ?Cavernous lymphangioma. DOI: http://dx.doi.org/10.3329/bjms.v11i4.12612 Bangladesh Journal of Medical Science Vol. 11 No. 04 Oct12